Unmanned Aircraft Capture and Control Via GPS Spoofing - Kerns, Andrew J.; Shepard, Daniel P.; Bhatti, Jahshan A.; Humphreys, Todd E. (Journal of field robotics, 2014)
The theory and practice of unmanned aerial vehicle (UAV) capture and control via Global Positioning System (GPS) signal spoofing are analyzed and demonstrated. The goal of this work is to explore UAV vulnerability to deceptive GPS signals. Specifically, this paper (1) establishes the necessary conditions for UAV capture via GPS spoofing, and (2) explores the spoofer's range of possible post‐capture control over the UAV. A UAV is considered captured when a spoofer gains the ability to eventually specify the UAV's position and velocity estimates. During post‐capture control, the spoofer manipulates the true state of the UAV, potentially resulting in the UAV flying far from its flight plan without raising alarms. Both overt and covert spoofing strategies are considered, as distinguished by the spoofer's attempts to evade detection by the target GPS receiver and by the target navigation system's state estimator, which is presumed to have access to non‐GPS navigation sensor data. GPS receiver tracking loops are analyzed and tested to assess the spoofer's capability for covert capture of a mobile target. The coupled dynamics of a UAV and spoofer are analyzed and simulated to explore practical post‐capture control scenarios. A field test demonstrates capture and rudimentary control of a rotorcraft UAV, which results in unrecoverable navigation errors that cause the UAV to crash.